Effect of Heat Input with Current Variation on Weld Overlay GTAW Method with ERNi-CI and ERNiFe-CI Fillers on Mechanical Properties and Micro Structure of Main Cap Product - Laisa, Muhammad Ikbal; Sulistijono, Sulistijono; Awali, Jatmoko (IPTEK Journal of Proceedings Series, 2018)
Weld overlay is one of veneering method that do by welding on the base metal, so there is wear resistant, additional layer and corrosion resistant. Vibration load that work continue on engine block causing worn out on the components that be in the engine block, one of which occurs on both sides of the main cap that directly intersect to the engine block, however it needed an appropriate repair method that is weld overlay method that giving additional layer and wear resistant. This research is using filler ERNi-CI dan ERNiFe-CI on weld overlay method GTAW with current variation on main cap that made from nodular cast iron. Trials that did is conducted metallography and hardeness. The observation result of metallography show that micro structure in HAZ area and base metal contain more ferrite on the lower current. The more heat input however the more it decreasing hardeness value on weld metal and fusion line. This is caused by the more heat input, however cooling that happens become slow. The hardeness value of welding filler ERNiFe-CI is more high than the hardeness value of welding filler ERNi-CI effect of influence the numbers of nickel composition on the filler.